P.112 Permanent isolated micrographia from traumatic basal ganglia injury. (June 2019) - Persad, A; Mehta, V
Abstract : Background: Micrographia is a rare neurological finding in isolation. Most cases of isolated micrographia have been found in association with focal ischemia of the left basal ganglia. Methods: We present a case of post-traumatic micrographia stemming from contusion to the left basal ganglia. We performed a detailed analysis of the patient's writing at three-year follow-up. Results: A halthy 15 year old male was admitted following a BM accident. CT showed contusion to the left basall ganglia/external capsule. MRI was negative for underlying lesion. He had a short stay in the ICU and then was discharged. Two years later, he expressed concern regarding difficulty with sma, cramped writing at school. Writing analysis revealed micrographia with spontaneous printing as well as printing to dictation, but not with copied English nor Japanese writing. Conclusions: Isolated micrographia is a rare neurological finding. We present the incidence of this symptom folllowing gliding contusion to the et basal ganglia and external capsule.